Compatibility Of Textbook "English In Focus" With Content Standard And Communicative Competence - Istiqomah, Dyaswari (2012)
This research is aimed to describe the compatibility between the content of the textbook English in Focus with the content standard and five competences of Celce murcia's model of communicative competence, they are discourse competence, linguistic competence, actional competence, sociolinguistic competence, and strategic competence. This research is qualitative research . The object of this research is English textbook named English in Focus that published by CV Putra Nugraha written by Artono Wardiman and friends. The writer analyzes the textbook of nineth grade students. In collecting the data, the writer uses documentation method. The data are analyzed and categorized into four degrees of compatibility based on the theory of Suharsimi which involves very good, good, fair and poor. The findings show that only one material suggested in content standard is not covered in the textbook English in Focus, that is Label that belongs to short functional text. It means that 93% of the suggested materials in content standard have been covered. This percentage describes that the degree of compatibility between the content of the textbook and the content standard is very good.The findings also show that among the five competences and its components of communicative competence, some components are not covered in the textbook English in Focus. Hence, the degree of compatibility of each competence is various. Discourse competence places the highest position with its percentage is 100%. So that its degree of compatibility is very good. The percentage of Linguistic competence is 60% and the degree of compatibility is good. The percentage of actional competence is 86% so that its degree of compatibility is very good. While 50% of the components of sociocultural competence are covered so that it places this competence in the fair degree.The lowest degree is placed by strategic competence of which degree of compatibility is poor with its percentage is 20 %. So, considering the result above, the writer can conclude that the materials in English in Focus are sufficient enough to fullfil the content standard.In the other hand, they are not sufficient enough to develop the students' communicative competence, especially in developing sociolinguistic and strategic competence.